Effectiveness of Behavioral Ivan Pavlov Conservation with Modeling Techniques to Increase Characters Organize Work Neatly Through Lesson Study - Ade Oki Agus Pradana; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov modeling techniques to improve the character of organize work neatly through lesson study. This type of research is quasi-experimental with pre-test and post-test control group design. The samples were 32 students with df 31. Data collection methods using questionnaires characters organize work neatly totaling 30 items.The results of the data analysis is the value of thit 7,826 > ttab 2,039 so Ho rejected and Ha accepted. So there are significant difference. It can be concluded that behavioral counseling Ivan Pavlov effective modeling techniques to improve the character of organize work neatly.